Analisis Strategi Pemasaran Spare Part Motor Pada Bengkel Sentral Jaya Ende - Rosmiati, Rosmiati; Langga, Lambertus; Dua Mea, Maria Helena Carolinda (SCIENTIFIC JOURNAL OF MANAGEMENT AND BUSINESS (SJMB), 2021)
The purpose of this research is to find out the marketing strategy of motor spare parts workshop at The Jaya Ende Central Workshop. By analyzing strength, weaknesses, opportunities and threats possessed by the Workshop. The type of research used is qualitative descriptive, analytical techniques data used are SWOT Matrix, SWOT Analysis Diagram, Internal Factor Analysis Strategy, as well as External Factor Analysis Strategy. The population researched is Bengkel Sentral Jaya Ende with a total of 10 employees, and the number of respondents taken as many as 10 people. From the calculation of the IFAS table strength is higher than weakness, as well as from efas table calculations the odds are smaller than the threat so the point is in quadrant IV. The results showed that the marketing strategy of motor spare parts at Bengkel Sentral Jaya Ende is a strategic location that can help marketing at the workshop, as well as the quality of goods and the quality of service make customers comfortable to buy spare part products at Bengkel Sentral Jaya Ende.